Bioprospeksi dan Identifikasi Molekuler Bakteri yang Berasosiasi dengan Alga Hijau sebagai Penghasil Senyawa Antibakteri - Endang_Kusdiyantini, Rizky Panji_Nugroho (Prosiding KPSDA, 2015)
Bacteria are ubiquotus and could grow in various environments, including those associated with marine organisms such as algae, sponge, sea grass and soft corals. For these organisms, bacteria help building their active defense mechanisms by producing secondary metabolites such as antibacterial compounds. This research aimed to study the potency of seaweed-associated bacteia in producing antibacterial compounds. The seaweed used were Halimeda macroloba, Caulerpa racemosa dan Ulva sp. The results of isolation found five bacteria: one from H. macroloba, three from C. racemosa, and one from Ulva sp. Antibacterial assays was done by measuring inhibition zone to the growth of three bacteria: Escherichia coli, Staphylococcus aureus, dan Pseudomonas aeruginosa. Bacteria Isolated from H. macroloba showed the highest inhibition zone towards P. aeruginosa of 18.1 mm. Using molecular 16S rRNA identification, this isolate showed similarity to Idiomarina fontislapidosi strain HME8844. Biochemical tests showed that this isolate Â Â was negative to ferment the sugar of arabinose, fructose and sucrose, and also negative to amylum hidrolysis.